Monastic Imprisonment in Justinian's Novels - Hillner, Julia (Journal of early Christian studies, 2007)
In the period between 542 and 556 C.E. Justinian issued a number of laws that prescribed monastic imprisonment as punishment for both higher clergy and members of the lay elite. Through this legislation, the emperor introduced into Roman law the unprecedented concept of corrective imprisonment as a penalty. Starting from a detailed analysis of the laws, this article demonstrates how the emperor's innovations built upon both traditional legal practices and on more recent ecclesiastical and monastic ideals. With monastic imprisonment, Justinian adapted the Roman custom of domestic internment as a substitute for the penalty of exile for elite criminals. The reason for using monasteries, rather than private households, to provide this public service of prisoner internment may, on the one hand, have been practical. Ideals of hospitality within a Christian monastic context and imperial influence especially over Constantinopolitan monasteries may have encouraged Justinian to believe that monasteries were far less likely to avoid an obligation to host an exile convict than private households. On the other hand, the emperor also saw monastic imprisonment as offering additional, historically unprecedented benefits over traditional domestic internment. As the emperor tried to make sure in his own legislation on monastic life, monasteries ideally provided an institutional and architectural framework, as well as a guiding penitential ideology based on an ideal of correction, which not only offered the opportunity for enhanced supervision, but also for spiritual correction of the criminal. Justinian's innovations may have been inspired by the established use of monasteries as penitential space for failing clerics in ecclesiastical legislation. However, his specific aim in using monasteries as places of penance, for which an ecclesiastical precedent does not exist, seems to have been to police the sexual promiscuity which he discerned among the married laity at his own court.